Proposed guidelines for libraries for the blind in the Philippines based on the British Council of Museums, Archives, and Libraries' Best Practice Manual for Library Service for Visually Impaired People and evaluation of the Philippine National School for the Blind - Paraan, Ronald Gonin C. (2008)
Libraries have always been an important institution in society as an accessible source and repository of knowledge. Accessing and using libraries are fairly simple for the regular library users but the situation is different for people who have visual impairments. Visually Impaired People are generally unable to use the regular materials found in a common library and the best solution to this drawback is to provide the proper library services that fit the need of the visually impaired.